Construction of second generation protease‐deficient hosts of Bacillus subtilis for secretion of foreign proteins. Issue 8 (24th April 2019) - Zhao, Leizhen; Ye, Bin; Zhang, Qi; Cheng, Dan; Zhou, Chaoyang; Cheng, Shan; Yan, Xin
Abstract: Although one of the major factors limiting the application of Bacillus subtilis as an expression host has been its production of at least eight extracellular proteases, researchers have also noticed that some proteases benefited the secretion of foreign proteins at times. Therefore, to maximize the yield of a foreign protein, the proteases should be selectively inactivated. This raises a new question that how to identify the favorable and unfavorable proteases for a target protein. Here, an evaluation system containing nine mutant strains of B. subtilis 168 was developed to address this question. The mutant strain PD8 has all the eight proteases inactivated whereas each of the other eight mutant strains expresses only one kind of these eight proteases. The target protein is secreted in these nine mutant strains; if the production of target protein in a mutant strain is higher than that in strain PD8, the corresponding protease is regarded as favorable. Accordingly, the optimal protease‐deficient host is constructed through inactivating the unfavorable proteases. The effectiveness of this system was confirmed by expressing three foreign proteins. This study provides a strategy for improving the secretion of a foreign protein in B. subtilis through tailoring a personalized protease‐deficient host. Abstract : Although one of the major factors limiting the application of Bacillus subtilis as an expression host has been its production of at least eight extracellular proteases, researchers have also noticed that some proteases benefited the secretion of foreign proteins at times.